Fractional q-Integral Operators for the Product of a q-Polynomial and q-Analogue of the I-Functions and Their Applications. (31st October 2021) - Vyas, V.K.; Al-Jarrah, Ali A.; Suthar, D. L.; Abeye, Nigussie
Abstract : In this article, we derive four theorems concerning the fractional integral image for the product of the q -analogue of general class of polynomials with the q -analogue of the I -functions. To illustrate our main results, we use q -fractional integrals of Erdélyi–Kober type and generalized Weyl type fractional operators. The study concludes with a variety of results that can be obtained by using the relationship between the Erdélyi–Kober type and the Riemann–Liouville q -fractional integrals, as well as the relationship between the generalized Weyl type and the Weyl type q -fractional integrals.